Peningkatan Keterampilan Editing Video melalui Workshop Become Professional Editor - Dani Arifudin; Deuis Nur Astrida; M. Syaiful Amin (PT. Karya Inovatif Nusantara, 2026)
This community service activity aimed to improve students’ video editing skills through the “Become Professional Editor” workshop. The training was conducted using a hands-on practice approach that integrated creativity development, understanding of video production workflows, and the introduction of professional working standards in the digital creative industry. The workshop materials covered creative idea development, video production and post-production processes, the use of editing platforms and tools, the development of professional work habits, and project management aspects such as timeline preparation, quotations, licensing, work contracts, invoicing, and project handover. The implementation methods included lectures, demonstrations, interactive discussions, and independent video editing practice. The results of the activity indicated an improvement in participants’ understanding of professional video editing processes as well as increased motivation to develop competencies in the digital creative industry. Participants also gained insights into creative economic opportunities through video editing and digital content production skills. Therefore, this workshop served as an effective medium for developing competencies relevant to the current needs of the creative and digital media industries.